Hubungan Pola Asuh Orang Tua Dengan Kepribadian Anak Usia 6-12 Tahun - Fatayati, Aminatul; Kusumawati Priyono, Putri; Catur Yuliani, Feri; Kusuma Putri, Erni (INVOLUSI: Jurnal Ilmu Kebidanan, 2025)
There are 20% children in the world's have emotional and behavioral problems. One factor is parenting parents. Parenting that is incompatible with the child's development will increase the incidence of emotional and behavioral problems.To know the correlation of parenting parents with personality children ages 6-12 years at Polengan Village Pagutan Manyaran Wonogiri. This type of research descriptive correlative with cross sectional quantitatively. The population in this research 154 people. Sampling techniques is purposive sampling with sample of 60 people. The instruments used in this study is a questionnaire. This research using chi-square. The pearson chi-square 0.327 with ρ value 0.011 meaning ρ < α (0.05). Authoritarian parenting is 30%, permissive is 25% and democratic 45%. The extrovert personality 71.7% and introvert personality 28.3%. The relationship of two variables that are categorized as low. There is a correlation of parenting parents with personality children ages 6-12 years at Polengan Village Pagutan Manyaran Wonogiri.